ANALISIS PENGARUH STRUKTUR KEPEMILIKAN DAN DEWAN KOMISARIS TERHADAP KINERJA PERUSAHAAN (Studi Empiris pada Perusahaan Energi yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2022) - Jovan Axel; Paulus Theodorus Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2023)
This study aims to examine the effect of foreign ownership, financial company ownership, managerial ownership, board size, the proportion of independent commissioners, and the proportion of female commissioners on company performance. This research uses secondary data that comes from the financial reports of all energy sector companies listed on the Indonesia Stock Exchange (IDX) in 2020-2022. The research sample was taken by using purposive sampling method. A total of 45 companies were tested with details of 135 samples throughout the three years of the study. The analytical method used is the Partial Least Square (PLS) analysis method. The results of this study indicate that foreign ownership, financial institution ownership, managerial ownership, board size, the proportion of independent board, and the proportion of female board were found to have no effect.